The effect of educational videos "they are us" on stigmatizing people with mental disorders - Sifa Eka Wardani; Suci Ratna Estria (Proceedings Series on Health & Medical Sciences, 2020)
Stop stigma educational video “they are us” aims to eliminating the stigma in fikes students and shifting the negative stigma  be a positive stigma against people with mental disorders. This study aims to determine the stop-stigma educational video entitled “They Are Us” towards students of Health and Science Faculty. This study used a quasi-experimental method with one-group pre-test and post-test designs. The research sample was 166 respondents, using cluster random sampling technique. The instrument used was a stigma questionnaire sheet adapted from research conducted by Sasra (2018) in Padang. The results of this study show the stigma of pre-test (39,40) and post-test  (62.28). The result of the Wilcoxon pre-test, post-test of stigma indicate a significance level of 0.000 (P 0.05).  In conclusion There is a significant effect of giving the stop-stigma educational  video entitled “They Are Us” towards students of Health and Science Faculty.